Policy on Fulfilling the Rights of Persons with Disabilities in Indonesia: Quo Vadis? - Simanjuntak, Jeremia Gom Gom Parulian (The Center for Disability Studies and Services Brawijaya University, 2021)
The Law on persons with disabilities is an aspiration and hope in achieving equality, equal rights and opportunities for persons with disabilities in Indonesia. The implementation of this law is currently not well implemented and has not succeeded in creating equality, equal rights and opportunities for persons with disabilities in their social life. Persons with disabilities still experience various difficulties in their social life and their rights are often neglected. The method used in writing this article is a qualitative method with a descriptive approach. The data collection technique is done by studying the literature. This article is intended to provide an overview of the implementation of the law on persons with disabilities in Indonesia and provide an overview of the situation of persons with disabilities after the law was passed.